Integrated Small Intestine Microbiota and Serum Metabolomics Reveal the Potential Mechanisms of Wine Steaming in Alleviating Rhubarb-Induced Diarrhea - Bai YY; Tian R; Qian Y; Zhang Q; Zhao CB; Yan YG; Zhang L; Yue SJ; Tang YP (Dove Medical Press, 2024)
Ya-Ya Bai,1 Rui Tian,1 Yan Qian,2 Qiao Zhang,1 Chong-Bo Zhao,1 Yong-Gang Yan,1 Li Zhang,3 Shi-Jun Yue,4 Yu-Ping Tang1 1Key Laboratory of Shaanxi Administration of Traditional Chinese Medicine for TCM Compatibility, and State Key Laboratory of Research & Development of Characteristic Qin Medicine Resources (Cultivation), and Shaanxi Collaborative Innovation Center of Chinese Medicinal Resources Industrialization, and Shaanxi Traditional Chinese Medicine Processing Technology Heritage Base, Shaanxi University of Chinese Medicine, Xi'an, 712046, People's Republic of China; 2Suzhou Institute for Drug Control, Suzhou, Jiangsu Province, 215000, People's Republic of China; 3Hanlin College, Nanjing University of Chinese Medicine, Taizhou, Jiangsu Province, 225300, People's Republic of China; 4International Joint Research Center on Resource Utilization and Quality Evaluation of Traditional Chinese Medicine of Hebei Province, Hebei University of Chinese Medicine, Shijiazhuang, 050200, People's Republic of ChinaCorrespondence: Qiao Zhang, Shaanxi University of Chinese Medicine, Shiji Avenue, Xi Xian New District, Xi'an, 712046, People's Republic of China, Tel +86-15895973680, Fax: +86-02938185061, Email 18700081184@163.comBackground: Long-term use of rhubarb (RH) commonly leads to diarrhea, which can be alleviated by steaming with wine. However, the specific mechanism by which wine steaming alleviates RH-induced diarrhea remains unknown.Objective: This study aims to reveal the underlying mechanisms of wine steaming in alleviating RH-induced diarrhea by examining small intestinal flora and serum metabolomics.Methods: Major anthraquinone and anthrone components were detected using ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). Eighty-four ICR mice were randomly divided into control, RH, and RH steamed with wine (PRH) groups and were administered RH and PRH (1, 4, and 8 g/kg, i.g). for 14 consecutive days. Histopathological analysis was performed using hematoxylin-eosin staining. Levels of inflammatory factors and tight junction proteins, zonula occludens-1 (ZO-1) and occludin, in the small intestine were measured. The small intestine content was analyzed using 16S rRNA sequencing, and UPLC-MS was used to analyze endogenous metabolites.Results: Levels of major anthraquinone and anthrone components decreased in PRH. Both RH and PRH groups showed varying degrees of loose stools and increased fecal water rates; the RH group exhibited more severe effects. Compared with the control group, RH caused small intestine injuries, increased levels of inflammatory cytokines, downregulated the expression of ZO-1 and occludin, and induced gut microbiota (GM) imbalance. The relative abundance of Lactobacillus decreased, while the relative abundance of Shigella and Streptococcus increased. However, PRH had a milder impact than RH. The glycerophospholipid metabolic pathway was involved in this effect. The levels of inflammatory cytokines and potential metabolites (sn-glycero-3-phosphoethanolamine) were positively correlated with Streptococcus infection, while the levels of ZO-1 and occludin were negatively correlated with Streptococcus infection. GM imbalance and abnormal glycerophospholipid metabolism contributed to impaired intestinal barrier function and inflammatory factor release, which may underlie RH-induced diarrhea, though PRH had a weaker effect.Conclusion: PRH alleviated RH-induced diarrhea by recovering GM balance, reducing ZO-1 and occludin expression, and decreasing the release of inflammatory factors. This mechanism may be linked to the reduced anthraquinone content. This study is the first to explore the mechanism of wine steaming in alleviating RH-induced diarrhea through small intestinal flora and serum metabolomics. It provides data to support the broader clinical use of RH and its safer application. Keywords: gut microbiota, metabolomics, wine steaming, diarrhea, rhubarb